Field experiment on occupant comfort on a tall building in Metro Manila - Columna, Jenalyn M.; Tungol, Ian Howell S. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Due to the continuous growth of the Philippine economy combined with the advancements in the structural systems, more and more high rise building are being constructed which are made up of high strength but lightweight materials. These buildings are characterized with low natural frequencies, making them very susceptible to wind induced building motion. These motions may then cause discomfort and task disruption on the building's occupants. Using the Architectural Institute of Japan Code (AU Code), comfort analysis was done with two primary inputs, the frequency of tile structure and the peak acceleration, to assess tile comfortability of Tower A. A field test was done to get the acceleration versus time data of Tower A. This recorded data was then transformed into the frequency domain using tile Frequency Domain Decomposition method which was later on validated by structural model using the ETABS program and the NSCP Provision. Using the graph by the AU Code, it was showm that the data points corresponding to Signal No. 3 and Signal No. 4 typhoon wind speeds lie along the H-60 and H-90 curve respectively. It may then concluded, that tile occupants of Tower A may feel discomfort when the building is subjected to a Signal No.3 and Signal No.4 typhoon. This is because it can be argued that when there is high perception to motion by the building occupants (say 90% of tile occupants of a building), this may lead to occupants feeling discomfort. This research alone does not prove that the National Structural Code of the Philippines (NSCP) really needs to be updated since there are still many missing components in this study regarding occupant comfort. Other procedures should be done to properly conclude that human comfort criterion should really be incorporated in our current design code.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Tall buildings -- Aerodynamics; Tall buildings -- Vibration -- Philippines -- Manila; Human comfort